The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0034355213519681
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Job Placement Provider Decisions in Vocational Rehabilitation

Abstract: A modified consensual qualitative research approach was taken to determine factors that influence job placement services in selected state Vocational Rehabilitation agencies. Thirty-five counselors, supervisors, and administrators participated in semistructured interviews on job placement and how they determine whether the counselor or another professional (e.g., in-house placement specialist, community rehabilitation provider) provides the direct service. Results indicated that several factors were noted by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…With the passage of the WIOA legislation, there is an expectation that counselors will be more involved in business development activities than in the past. Previous research has documented the lack of comfort some counselors have with job development and working with employers (Fleming et al, 2014; Schultz, 2008), and that was confirmed with counselors in the present study. Agencies should evaluate how much support they are providing to counselors for business development activities and ensure that their level of support is adequate for their expectations related to business engagement.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…With the passage of the WIOA legislation, there is an expectation that counselors will be more involved in business development activities than in the past. Previous research has documented the lack of comfort some counselors have with job development and working with employers (Fleming et al, 2014; Schultz, 2008), and that was confirmed with counselors in the present study. Agencies should evaluate how much support they are providing to counselors for business development activities and ensure that their level of support is adequate for their expectations related to business engagement.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the fact that a majority of agencies currently employ business relations specialists (i.e., staff whose primary role is to interact with businesses), most counselors are also responsible for business development activities (Haines et al, 2018; McDonnall, 2017). Even though working with businesses is an essential job function, some counselors are uncomfortable about interacting with employers (McDonnall, 2014; Fleming, Phillips, Kaseroff, & Huck, 2014; Schultz, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative researchers typically: (a) involve participants in the data collection process; (b) ensure that data are collected in a naturalistic setting with researchers and participants interacting in a face-to-face manner; (c) recognize researchers as the key data collection "instruments"; (d) include multiple sources of data in the analysis; (e) consider the research process to be emergent and therefore conduct data analysis inductively; (f) are concerned with the meaning participants hold regarding the issue under study; (g) interpret what they see, hear, and understand; and (h) try to develop a complex picture of the issue (Creswell, 2007;Denzin & Lincoln, 2005). Qualitative approaches traditionally used in research include narrative, phenomenological, grounded theory, ethnographic studies, and case studies; although CQR methodology is now also being utilized by rehabilitation researchers (Fleming, Phillips, Kaseroff, & Huck, 2014). There are often commonalities between qualitative methods and the approaches noted here are intended to provide a basic overview rather than underscore distinctiveness from quantitative methods.…”
Section: Qualitative Research Approachesmentioning
confidence: 99%